Development of a Model of Care Management for COVID-19 Patients in Crisis at Krathumbaen Hospital, Samutsakhon Province, and Evaluation of Outcomes - Kaewinchai , Rachada; Nammong, Juthatip; Pheerawasthanawut , Nantipak (Journal of Nursing, Siam University, 2024)
Objectives To develop a management model for COVID-19 patients in critical condition at Krathum Baen Hospital, Samut Sakhon Province, and evaluate the outcomes. Methods This study is research and development. The management components in four areas include facility and environmental management, manpower ratio, personnel development, and equipment. The sample groups are divided into 37 professional nurses working in the Semi ICU Cohort ward and 347 COVID-19 patients registered for treatment at the Semi ICU Cohort ward. The research tools used include a nursing protocol for ventilator-assisted patients, a nursing protocol for patients receiving high-flow nasal cannula oxygen therapy, a survey on nursing practices for ventilator-assisted patients and patients receiving high-flow nasal cannula oxygen therapy, a satisfaction questionnaire for professional nurses regarding the management model for COVID-19 patients in critical condition, a perception questionnaire on self-competence in nursing COVID-19 patients in critical condition, and an outcome recording form. The content validity index (CVI) is .91, .89, .89, .83, and .88, respectively. The research was conducted from January to June 2022, and data analysis was performed using descriptive statistics and Chi-square tests. Results The research findings on nursing outcomes revealed that the infection rate of COVID-19 among professional nurses, while working in critical COVID-19 patient care, was 0. Overall satisfaction with the nursing management approach for critical COVID-19 patients was high (mean 3.76, SD=0.43), and confidence in caring for critical COVID-19 patients was rated as good (mean 4.05, SD=0.60). When comparing patient outcomes, it was found that the mortality rate of COVID-19 patients and the incidence rate of complications from being on HFNC before and after the development of nursing management approaches differed significantly statistically (P<.05). Conclusion The development of nursing management for critical-care Covid-19 patients Krathumbaen Hospital, Samutsakhon Province is an efficient nursing service system. The research findings should be utilized to enhance the quality of nursing care.